ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL DAN MENENGAH (IKM) DI KOTA PALU PERIODE 2000-2013 - Fauziah, Fauziah (Katalogis, 2015)
This study aimed to determine the role of small and medium industries in employment absorption and the factors that affect small and medium industries in employment absorption. This study was conducted on IKM in Palu, data used in this study are primary and secondary data at 2000-2013. Data were obtained from the Department of Industry, Trade and Cooperatives (Disperindakop) of Palu, Regional Development Planning Agency (Bappeda) of Palu, as well as from the Central Bureau of Statistics (BPS) Palu. The analysis tool used is descriptive analysis. Descriptive analysis showed that the value of capital affect employment in the city of Palu, not according to economic theory. Besides that two variables such as production values and also wages diindikatorkan through UMP also affects or has a positive relationship with employment absorption. the result of this this analysis of wageÂ  is not consistent with the theory that the higher wages paid to workers it will reduce the amount of labor demanded. This can be explained that in the real wages received by workers still under the provisions of the UMP Sulteng, so it is insignificant. beside that the number of workers who work on each IKM relatively little.